Colorectal adenocarcinoma‐derived EGFR mutants are oncogenic and sensitive to EGFR‐targeted monoclonal antibodies, cetuximab and panitumumab. Issue 8 (9th July 2019) - Kim, Nayoung; Cho, Daseul; Kim, Hyunjin; Kim, Sujin; Cha, Young‐je; Greulich, Heidi; Bass, Adam; Cho, Hyun‐Soo; Cho, Jeonghee
Abstract : Somatic mutations of epidermal growth factor receptor (EGFR) occur in 3% of colorectal cancer (CRC) patients. Here, through systematic functional screening of 21 recurrent EGFR mutations selected from public data sets, we show that 11 colon cancer‐derived EGFR mutants (G63R, E114K, R165Q, R222C, S492R, P596L, K708R, E709K, G719S, G724S and L858R) are oncogenic and able to transform cells in a ligand‐independent manner. We demonstrate that cellular transformation by these mutants requires receptor dimerization. Importantly, the EGF‐induced and constitutive oncogenic potential of these EGFR mutants are inhibited by cetuximab or panitumumab in vivo and in vitro . Taken together, we propose that a subset of EGFR mutations can serve as genomic predictors for response to anti‐EGFR antibodies and that metastatic CRC patients with such mutations may benefit from these drugs as part of the first‐line therapy. Abstract : What's new? Treating metastatic colorectal cancer patients with epidermal growth factor receptor (EGFR)‐directed monoclonal antibodies is promising, but achieves a clinical response in only 10–20% of unselected patients. The authors identified a subset of somatic EGFR mutations that are oncogenic in colorectal adenocarcinoma models and sensitive to EGFR‐directed antibody treatment. These EGFR mutations may serve as predictors for response to anti‐EGFR antibodies in colorectal adenocarcinoma.